Flirtation and courtship in nineteenth century British culture.
1 online resource (646 pages)
Keywords: This is volumetwo of athree-volume set that brings together a rich collection of primary source materials on flirtation and courtship in the nineteenth-century. Introductory essays and extensive editorial apparatus offer historical and cultural contexts of the materials included Throughout the long nineteenth-century, a woman⁰́₉s life was commonly thought to fall into three discrete developmental stages; personal formation and a gendered education; a young woman⁰́₉s entrance onto the marriage market; and finally her emergence at the apogee of normative femininity as wife and mother. In all three stages of development, there was an unspoken awareness of the duplicity at the heart of this carefully cultivated femininity. What women were taught, no matter their age, was that if you desired anything in life, it behooved you to perform indifference. This meant that for women, the art of flirtation and feigning indifference were viewed as essential survival skills that could guarantee success in life. These three volumes document the many ways in which nineteenth-century women were educated in this seemingly universal wisdom, but just as frequently managed to manipulate, subvert, and navigate their way through such proscribed norms to achieve their own desires. Presenting a wide range of documents from novels, memoirs, literary journals, newspapers, plays, poetry, songs, parlour games, and legal documents, this collection will illuminate a far more diverse set of options available to women in their quest for happiness, and a new understanding of the operations of courtship and flirtation, the "central" concerns of a nineteenth-century woman⁰́₉s life. The volumes will be of interest to scholars of history, literature, gender and cultural studies, with an interest in the nineteenth-century.